Geriatric nutritional risk index as a prognostic indicator in elderly patients with early colorectal cancer undergoing endoscopic submucosal dissection. Issue 3 (10th August 2021) - Kato, Minoru; Hayashi, Yoshito; Fukuda, Hiromu; Yamaguchi, Shinjiro; Inoue, Takuya; Ogiyama, Hideharu; Kitamura, Shinji; Komori, Masato; Yamamoto, Katsumi; Yamamoto, Masashi; Nagai, Kengo; Nakahara, Masanori; et al.
Abstract : Objectives: Data on the long‐term outcomes of endoscopic submucosal dissection (ESD) performed in elderly patients with early colorectal cancer (CRC) are limited. We analyzed the prognosis of elderly CRC patients, not only from the viewpoint of treatment curability but also from the patients' baseline physical condition assessed by several indexes. Methods: A retrospective analysis of 729 patients aged ≥75 years who underwent ESD for Tis/T1 CRC in 16 institutions was conducted. The patients were classified into three groups based on curability: curative ESD (Group A, n  = 582), non‐curative ESD with additional surgery (Group B, n  = 60), and non‐curative ESD without additional surgery (Group C, n  = 87). Overall survival (OS) was compared among the groups, and factors associated with reduced OS were investigated. Results: The median follow‐up periods in Groups A, B, and C were 41, 49, and 46 months, respectively ( P  = 0.62), during which 92 patients died. Two patients (0.3%) in Group A, none (0%) in Group B, and three (3.4%) in Group C died of CRC. Three‐year OS rates in Groups A, B, and C were 93.9%, 96.1%, and 90.1%, respectively, without a significant difference ( P  = 0.07). Multivariate analysis indicated low (<96.3) geriatric nutritional risk index (GNRI) as the sole independent predictor for reduced OS (hazard ratio 3.37; 95% confidence interval 2.18–5.22; P  < 0.0001). Conclusions: Low GNRI, but not the curability attained by ESD, was independently associated with reduced OS in patients with early CRC aged ≥75 years.